DINAMIKA POPULASI DAN INTERAKSI ANTAR-SPESIES FLORA DAN FAUNA DI HUTAN ALAM DUSUN FENARUA DESA PARBULU KECAMATAN WAILATA KABUPATEN BURU PROVINSI MALUKU - Yulianus Dominggus Komul; Febian Filiph Tetelay (Jurnal Sylva Scienteae, 2024)
Population dynamics and interactions between species of flora and fauna in natural forests are a process to determine the potential of biological natural resources and have a very important role in maintaining ecosystem balance and supporting life in general, helping to maintain ecosystem balance. Each species in an ecosystem has a unique role in nutrient cycling, decomposition, and climate change. The higher the level of biodiversity, the more stable the ecosystem is against disturbance and change, providing resistance to environmental change or disease attacks. Buru Island is one of the many islands located in Maluku province which has very large and diverse natural forest potential which certainly has a positive influence on its biodiversity value. Through research conducted in the natural forest area of Fenarua hamlet, Parbulu Village with mixed secondary forest land cover with shrubs, it can be seen that the biodiversity value for vegetation is 1.2583%. with the category of species diversity being in moderate condition as evidenced by the species diversity index (H') criteria according to Hanon Winner 1954. Meanwhile, the types of animals found were recorded as 14 types of birds, 7 types of mammals, 5 types of reptiles, and 7 types found in Research locations were found in various abundance classes, either very common, common, frequent or uncommon